Perancangan Sistem Point of Sale (POS) untuk Meningkatkan Efisiensi Pengelolaan Penjualan dan Stok Barang - Maridaningsih, Siti; Setiawan, Agus; Nugroho, Setiya (Journal of Information System Research (JOSH), 2025)
Effective information delivery is crucial in business, especially in managing transactions and inventory. Multi Ban Secang Motorcycle Tire Shop still relies on conventional methods for transaction recording and inventory management, leading to errors in data entry, inventory discrepancies, and delayed reporting, which result in decreased customer satisfaction and revenue. To address these issues, this study designs and develops a Point of Sale (POS) system expected to enhance operational efficiency and support strategic decision-making. The aim of this research is to design a POS application that can be implemented at Multi Ban Secang Motorcycle Tire Shop to resolve various problems in inventory and transaction management. The developed POS system will provide more accurate data management, speed up transaction processes, and generate real-time sales and inventory reports. The research follows the SDLC waterfall model, consisting of five stages, from requirements analysis to system evaluation and maintenance. The results of the study show that the implementation of the POS system improves efficiency in transaction recording and inventory management, as well as accelerates report generation. The system also enables users to monitor data in real-time and minimizes recording errors. Testing with the User Acceptance Testing (UAT) method showed a high user acceptance rate, indicating that the POS application is effective in improving store operations and strengthening business competitiveness.